The Effect of Economic Sectors in the Palestinian Gross Domestic Product (Case Study: 1995-2014) - Sweis, Khalid Mohammad Hasan; Sabri, Tamer Bahjat; Suos, Nasoh Lutfi (International Journal of Economics and Financial Issues, 2018)
The purpose of this study was to recognize the effect of economic sectors and their impact on the Palestinian domestic product based on the data issued by the Palestinian Central Bureau of Statistics between 1995 and 2014. The researchers used the descriptive-analytical approach and stepwise multiple regression model to analyze the sectors. The study results showed that the impact factor of the services sector was (41%) being the least efficient in the Palestinian economy. This researchers called for starting more investments in the economic sectors, specially the agricultural one, as they play a vital role in gross domestic product. Keywords: Economic sectors, Gross Domestic Product, investment, Palestine. JEL Classifications: A10; A19